Narrow Linewidth All-Optical Microwave Oscillator Based on Torsional Radial Acoustic Modes of Single-Mode Fiber - Wen Wang; Wenjun He; Xinyue Fang; Yi Liu; Yajun You; Mingxing Li; Lei Yu; Qing Yan; Yafei Hou; Jian He; Xiujian Chou (Micromachines)
A Hz level narrow linewidth all-optical microwave oscillator based on the torsional radial acoustic modes (TR2,m) of a single-mode fiber (SMF) is proposed and validated. The all-optical microwave oscillator consists of a 20 km SMF main ring cavity and a 5 km SMF sub ring cavity. The main ring cavity provides forward stimulated Brillouin scattering gain and utilizes a nonlinear polarization rotation effect to achieve TR2,7 mode locking. By combining the sub ring cavity with the main ring cavity and utilizing the Vernier effect, the TR2,7 mode microwave photonic single longitudinal mode (SLM) output can be ensured. Meanwhile, the 6.281 Hz narrow linewidth of the TR2,7 mode is achieved by reducing the intrinsic linewidth of the passive resonant cavity. The acoustic mode suppression ratio and side mode suppression ratio of the TR2,7 mode were 43 dB and 54 dB, respectively. The power and frequency fluctuations of within 40 min were approximately ±0.49 dB and ±0.187 kHz, indicating good stability. At a frequency offset of 10 kHz, the TR2,7 mode had a low phase noise value of −110 dBc/Hz. This solution can be used in various fields, such as high-precision radar detection, long-distance optical communication, and high-performance fiber optic sensing.